2019
DOI: 10.3390/nu11102358
|View full text |Cite
|
Sign up to set email alerts
|

A Nutraceutical Rich in Docosahexaenoic Acid Improves Portal Hypertension in a Preclinical Model of Advanced Chronic Liver Disease

Abstract: Inflammation and oxidative stress play a key role in the pathophysiology of advanced chronic liver disease (ACLD) and portal hypertension (PH). Considering the current lack of effective treatments, we evaluated an anti-inflammatory and antioxidant nutraceutical rich in docosahexaenoic acid (DHA) as a possible therapy for ACLD. We investigated the effects of two-week DHA supplementation (500 mg/kg) on hepatic fatty acids, PH, oxidative stress, inflammation, and hepatic stellate cell (HSC) phenotype in rats with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 37 publications
2
9
0
Order By: Relevance
“…Additionally, a meta-analysis of randomized controlled trials found omega-3 supplementation decreased arterial stiffness in adults [35]. Finally, omega-3 fatty acids have anti-inflammatory and anti-oxidant properties [36][37][38], both of which could contribute to improved cerebrovascular health and higher blood flow during exercise in the older adults in the present study who reported taking supplements.…”
Section: Discussionsupporting
confidence: 48%
“…Additionally, a meta-analysis of randomized controlled trials found omega-3 supplementation decreased arterial stiffness in adults [35]. Finally, omega-3 fatty acids have anti-inflammatory and anti-oxidant properties [36][37][38], both of which could contribute to improved cerebrovascular health and higher blood flow during exercise in the older adults in the present study who reported taking supplements.…”
Section: Discussionsupporting
confidence: 48%
“…In a previous publication from our research group [82], we found that ACLD's pathophysiology involves a profound deregulation of the hepatic fatty acid profile. The analysis, performed in livers from healthy and cirrhotic rats, showed that, among other alterations, cirrhotic livers are markedly depleted in DHA.…”
Section: Tg-dha In Acldmentioning
confidence: 74%
“…As in many other diseases, oxidative stress plays a key role in the pathogenesis of ACLD, contributing to the deregulation of all hepatic cell types and the progression of fibrosis. Indeed, the use of TG-DHA for the treatment of experimental ACLD has shown promising results [82]. However, given the complexity of the disease, the therapeutic approach for ACLD has recently shifted from monotherapy to combination therapy.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…TAA was previously dissolved in saline solution at a concentration of 125 mg/ml and administered intraperitoneally at a dose of 250 mg/kg body weight. 21,22 Following the last TAA administration, animals with ACLD underwent a detoxification period of 2 to 5 days before beginning pharmacological treatment.…”
Section: Animal Models Of Advanced Chronic Liver Diseasementioning
confidence: 99%